Pain and psyche in a patient with irritable bowel syndrome: chicken or egg? A time series case report - Engel, Felicitas; Stadnitski, Tatjana; Stroe-Kunold, Esther; Berens, Sabrina; Schäfert, Rainer; Wild, Beate (BMC gastroenterology, 2021)
Irritable bowel syndrome (IBS) appears to have a bidirectional interaction with both depressive and anxiety-related complaints. However, it remains unclear how exactly the psychological complaints, at the individual level, are related to somatic symptoms on a daily basis. This single case study investigates how somatic and psychological variables are temporally related in a patient with irritable bowel syndrome.
Gesehen am 07.07.2022